Syndromes with aortic involvement: pictorial review - Zucker, Evan J. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
A variety of syndromes are associated with thoracoabdominal aortic pathologies. While these diseases are collectively rare, the presence of advanced or unusual aortic disease at a young age should raise suspicion of an underlying syndrome. Similarly, patients with a known syndrome require close monitoring in anticipation of future aortic disease. In this article, the syndromes most commonly encountered in clinical practice are reviewed, including Marfan syndrome (MFS) and other connective tissue disorders, Turner syndrome (TS), autosomal dominant polycystic kidney disease (ADPKD), neurofibromatosis (NF), Williams syndrome (WS), Alagille syndrome (AGS), and DiGeorge syndrome (DGS). The distinct clinical, imaging, and management features of each disorder are discussed. Attention is focused on the unique patterns of aortic disease in each syndrome, emphasizing the role of recent imaging modalities and treatment strategies. Ancillary and distinguishing aspects of the syndromes that aid in diagnosis are also highlighted.